Strategies to Increase Profitability in Hospitality Industry - Deshmukh, Siddhant (ATLAS SkillTech University, 2024)
During my internship at Hotel Atithi, I was immersed in a dynamic and multifaceted environment within the hospitality industry. My responsibilities encompassed various facets of hotel management, including event coordination, guest services, and financial oversight. I had the privilege of managing diverse events, from birthday parties to corporate gatherings, ensuring their seamless execution while adhering to budgets. My role also involved analyzing guest feedback to enhance service quality, resulting in the implementation of an express check-in process and effective complaint resolution. Additionally, I actively contributed to optimizing the hotel's supply chain, successfully negotiating with suppliers to reduce procurement costs and enhance inventory efficiency. I further honed my financial acumen by assisting with budgeting, cost control, and financial reporting, contributing to the hotel's fiscal stability. Moreover, I actively participated in environmental conservation initiatives, fostering awareness among guests and staff about sustainable practices. Overall, my internship at Hotel Atithi provided a holistic learning experience, equipping me with skills in event management, financial acumen, guest services, and sustainability practices, all of which will be invaluable assets in my future endeavors within the hospitality and related industries.
Project Report on Strategies to Increase Profitability in Hospitality Industry (2022-24) Under the Guidance of Prof. Vipul Pancholi
Keywords: Dynamic; Corporate Gathering; Analysis